(untitled) (Revista Latino-Americana de Enfermagem, 2007)
This qualitative study aimed to understand how women having an abortion experience the nursing care they receive. The statements of 13 hospitalized women were analyzed through content analysis. The central category "Nursing care experienced in situations of abortion" was constituted from 4 subcategories: care centered in physical needs; fear of judgment in abortion situations; legal aspects defining care; the need for support in abortion situations. These women identified nursing care as based on physical aspects, without contemplating their individuality and specificities. Results indicated the need to create an environment that stimulates listening, helping these women to elaborate their feelings and allowing professionals to behave closer to these women's reality, in order to reduce their own desires and conflicts and contemplate the integrality of care.